MEMBANGUN KESADARAN DALAM KEPATUHAN MASYARAKAT UNTUK MEMBAYAR PAJAK - Amalia, Eka Wadzilah; Furqon, Imahda Khoiri (JURNAL PERPAJAKAN, 2023)
Taxes are folk fees to the state based on the law, so that it can be forced, by not getting a direct report. Taxes are collected based on legal norms to cover the production costs of collective goods and services to achieve general well-being. Rejection to pay, avoidance, or resistance to taxes in general include legal violations. Tax is one of the sources of government funds to carry out development, both the central government and regional government. If someone has fulfilled the subjective requirements and objective requirements, then it must pay taxes. In the Tax Act has been explained, if someone intentionally does not pay taxes that should be paid, then the threat of administrative sanctions and penalties criminal.